Strategy changes, principles remain: Why policy makers should stay focused on the SDGs - Rob van Tulder (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
Navigating sustainable FDI flows in a crisis-struck world presents a test of smart public-private alignment around a common agenda that goes beyond protectionist and risk-mitigation policies. Adhering to the principles-based frame of the SDG is - now more than ever - needed, but also increasingly feasible. This Perspective explains why and how.
Keywords: 330